International monetary reform - Walshe, Grahame (London : Macmillan, 1971)
This book describes the gold exchange standard monetary institutions and surveys the literature on the considered shortcoming of those institutions. The major part of the text is concerned with establishing vetting criteria for plans which aim to reform gold exchange standard institutions and a survey of the plans in the light of those criteria.
Bibliography: p. 82-85.
usc 15/08/18
Loans
Keywords: Monetary policy; International finance; Foreign exchange